Some results of the breeding and genetic studies of common wheat in the south-east of Kazakhstan (International Journal of Biology and Chemistry, 2014)
Increase productivity and quality of wheat by improving its genotype – one of the main problems of agriculture. Currently, using conventional methods of breeding and genetic research, such as mutagenesis, backcrossing selection and distant hybridization can increase the effectiveness of producing genetically improved crop forms. The fertility rate of soft wheat hybrids of wild species with T. timopheevi depends on the direction of crosses and genotype of varieties. Wild species as the parent component favorably affect a high percentage of tying grains.